“Nonlinear Dynamics - 2016” Conference - Bazhenov, V. A.; Pogorelova, O. S.; Postnikova, T. G. (КНУБА, 2016)
There is short description of problem state on nonlinear dynamics in this paper. Information about some contemporary journals and recent Conferences on this subject is given. Information about 5th International Conference on Nonlinear Dynamics which was holding in National Technical University “Kharkov Polytechnic Institute” in September 2016 and impression about it are presented.
Keywords: nonlinear dynamics; conference; vibroimpact system; discontinuous bifurcation.; 539.3